2011
DOI: 10.3324/haematol.2011.041483
|View full text |Cite
|
Sign up to set email alerts
|

Stability of human rapamycin-expanded CD4+CD25+ T regulatory cells

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe clinical use of ex vivo-expanded T-regulatory cells for the treatment of T-cell-mediated diseases has gained increasing momentum. However, the recent demonstration that FOXP3 + Tregulatory cells may contain interleukin-17-producing cells and that they can convert into effector cells once transferred in vivo raises significant doubts about their safety. We previously showed that rapamycin permits the ex vivo expansion of FOXP3 + T-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 36 publications
(59 reference statements)
4
62
0
2
Order By: Relevance
“…Freshly isolated Tregs from HD patients stained marginally more positively for IL-17 and after activation in IL-17-inducing cytokines (IL-2, IL-1b, IL-6, and TGF-b [32]), produced more IL-17 than those Tregs from HCs, but these differences did not reach statistical significance (Figure 4, A-C). After expansion ex vivo, low-level staining for IL-17 was observed in Tregs from both HCs and HD patients, with HD Tregs, as before, being slightly more positive for IL-17 ( Figure 4, D and E).…”
Section: Rapamycin Effectively Prevents Il-17 Production By Expanded mentioning
confidence: 70%
See 3 more Smart Citations
“…Freshly isolated Tregs from HD patients stained marginally more positively for IL-17 and after activation in IL-17-inducing cytokines (IL-2, IL-1b, IL-6, and TGF-b [32]), produced more IL-17 than those Tregs from HCs, but these differences did not reach statistical significance (Figure 4, A-C). After expansion ex vivo, low-level staining for IL-17 was observed in Tregs from both HCs and HD patients, with HD Tregs, as before, being slightly more positive for IL-17 ( Figure 4, D and E).…”
Section: Rapamycin Effectively Prevents Il-17 Production By Expanded mentioning
confidence: 70%
“…Nevertheless, this finding is the clearest indication yet that Treg-based cell therapy for renal allograft transplantation should use a Rapamycin-based protocol. Rapamycin is an ideal choice for Treg-based therapy in solid organ transplantation, because it preferentially expands the most stable Treg subpopulation (population I) and inhibits IL-17 production from other subpopulations (32,44). Rapamycin interferes with early T cell signaling events (Akt/mammalian target of rapamycin), which are critical in T cell fate decisions (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this concern, Treg lines were cultured in the presence of pro-inflammatory cytokines previously reported to favor Th17 conversion. 8,28 Two cytokine cocktails were selected: cocktail A (IL-1β, IL-2, IL-6 and TGF-β) and cocktail B (IL-2, IL-21, IL-23 and TGF-β). Analysis of supernatants from freshly isolated or 28-day untreated Tregs revealed that IL-17 production was increased by the addition of each cytokine cocktail.…”
Section: Treatment Of Tregs With Rapa Inhibits Their Conversion To Ilmentioning
confidence: 99%